Alignment Analysis of the Curriculum of the Tahfidz Darul Quran Al Haramain Pontianak Islamic Boarding School with the Independent Curriculum in the Contemporary Education Era - Iftiza, Fachria; Andriono, Eko; Liana, Liana; Warneri, Warneri (Program Pascasarjana UIN Sumatera Utara, 2024)
This research aims to analyze the conformity between the Tahfidz Darul Quran Al Haramain Pontianak Islamic Boarding School Curriculum and Merdeka Curriculum concept which started in the contemporary education era. The analytical research method used is descriptive with a qualitative approach. Data was collected through observation, interviews and documentation related to the curriculum implemented at the Tahfidz Darul Quran Al Haramain Pontianak Islamic Boarding School as well as the Merdeka Curriculum which is implemented nationally.The results of the analysis show that the Tahfidz Darul Quran Al Haramain Pontianak Islamic Boarding School Curriculum has several similarities and differences with the Merdeka Curriculum. Although both aim to strengthen the character and competence of students, the approaches, learning materials and evaluation methods used can vary. A number of aspects were also found in which the two curricula could complement each other and enrich the experience of the educational participants being raised. This research contributes to an understanding of the conformity between traditional approaches to Islamic education, as applied in Islamic boarding schools, and the modern education concept promoted by the Merdeka Curriculum. The implications of these findings can be used as a basis for developing holistic and inclusive educational strategies, combining traditional values with contemporary demands in an effort to prepare students to become competitive individuals with noble character in a global society.Penelitian ini bertujuan untuk menganalisis keselarasan antara Kurikulum Pondok Pesantren Tahfidz Darul Quran Al Haramain Pontianak dengan konsep Kurikulum Merdeka yang diperkenalkan dalam era pendidikan kontemporer. Metode penelitian yang digunakan adalah analisis deskriptif dengan pendekatan kualitatif. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi terkait kurikulum yang diterapkan di Pondok Pesantren Tahfidz Darul Quran Al Haramain Pontianak serta Kurikulum Merdeka yang diimplementasikan secara nasional. Hasil analisis menunjukkan bahwa Kurikulum Pondok Pesantren Tahfidz Darul Quran Al Haramain Pontianak memiliki beberapa kesamaan dan perbedaan dengan Kurikulum Merdeka. Meskipun keduanya bertujuan untuk memperkuat karakter dan kompetensi peserta didik, pendekatan, materi pembelajaran, dan metode evaluasi yang digunakan dapat bervariasi. Ditemukan juga sejumlah aspek di mana kedua kurikulum tersebut dapat saling melengkapi dan memperkaya pengalaman pendidikan peserta didik. Penelitian ini memberikan kontribusi dalam pemahaman tentang keselarasan antara pendekatan tradisional dalam pendidikan Islam, seperti yang diterapkan di pondok pesantren, dengan konsep pendidikan modern yang diusung oleh Kurikulum Merdeka. Implikasi temuan ini dapat digunakan sebagai dasar untuk mengembangkan strategi pendidikan yang holistik dan inklusif, menggabungkan nilai-nilai tradisional dengan tuntutan kontemporer dalam upaya mempersiapkan peserta didik menjadi individu yang berdaya saing dan berakhlak mulia dalam masyarakat global.